THE POLITICAL THOUGHT OF ABDUL WAHAB CHASBULLAH: CONTRIBUTIONS TO THE NATIONAL MOVEMENT AND THE CONCEPT OF STATEHOOD - Kusumoningtyas, Anggi Anggraeni (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2025)
This study comprehensively discusses Abdul Wahab Chasbullah's political thought and his contribution to the national movement and the development of the concept of statehood in Indonesia. Abdul Wahab Chasbullah is one of the most important figures in the intellectual history of Islam in Indonesia, particularly through his central role in the establishment of Nahdlatul Ulama (NU), the largest Islamic organization that continues to play a strategic role in the religious, social, and political life of the nation. His ideas on the relationship between religion and the state are based on moderate, open, and contextual Islamic principles, which are capable of addressing contemporary challenges without losing their fundamental values. Using a qualitative approach and literature review methods, this study examines various primary and secondary sources, including biographical books, works of thought by prominent figures, scientific journal articles, historical archive documents, and contemporary writings. This approach allows for an in-depth exploration of the dynamics of Abdul Wahab Chasbullah's thinking and how his ideas made a real contribution to the struggle for Indonesian independence and the formation of an inclusive national framework. His thoughts were not limited to religious discourse, but also included visionary socio-political strategies in fighting for independence and building a state system that respected plurality. The results of the research show that Abdul Wahab Chasbullah was a cleric who was not only fluent in religious knowledge, but also very sensitive to the socio-political developments of his time. His moderate and adaptive political views enabled him to build bridges between Islamic tradition and the growing spirit of nationalism during the colonial period. Through NU, he made Islam a moral force that helped drive the struggle for independence. He was active in various national organizations and used the media as a means of intellectual and political struggle. Thus, Abdul Wahab Chasbullah's political thought is not only an important historical legacy but also relevant as a reference for formulating policies and the direction of national development today. His inclusive attitude and contextual understanding of Islamic values serve as an important example for future generations in building a democratic, just, and culturally rooted nation.